Supporting innovating employees : how managerial coaching affects four dimensions of innovative work behavior - Pajuoja, Maria; Viitala, Riitta; Henttonen, Kaisa (Springer, 2025)
SMEs rely on innovation, and individual employees come up with and implement ideas to act as the microfoundations of organizational innovation. Managers play a critical role in encouraging employees’ innovative work behavior. However, thus far, this relationship has been studied utilizing a one-dimensional construct, and little is known about whether a determinant affects all phases of the innovation process equally. We investigate the effect of managerial coaching– managers coaching their employees to improve performance– on four dimensions of innovative work behavior. We show that managerial coaching positively influences innovative behavior in organizations, but is least important when employees explore ideas and most important when they implement ideas. We also find that employees tend to be more comfortable exploring and generating ideas than championing and implementing them, indicating innovation potential at the employee level which can be unlocked if managers know how to coach employees at the right time.
Keywords: Innovative work behavior (IWB); Employee innovation; Innovation process; Managerial coaching; Innovation management; fi=Henkilöstöjohtaminen|en=Human Resource Management|